1981
DOI: 10.1128/aem.41.2.459-465.1981
|View full text |Cite
|
Sign up to set email alerts
|

Survival of enteroviruses and coliform bacteria in a sludge lagoon

Abstract: Enteroviruses associate with aerobically and anaerobically digested sludge were determined before the addition of the sludge to a sludge lagoon. The fate of sludge-associated viruses was followed during detention of sludge in the lagoon and after application of sludge to land for disposal. While digested sludge was being added to the lagoon, enteroviruses were readily detected in grab samples of sludge from the lagoon. Sludge-associated viruses dropped to low or undetectable levels after disposal of sludge on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The EV distributions described here could also be reflective of differential persistence rates among EV species in municipal wastewater between households and primary treatment. Previous studies have reported variable rates of persistence among EV in wastewater sludge (54)(55)(56), but controlled studies comparing species-specific differences are lacking. Such information is necessary to help determine the relative levels of importance of seasonal shedding rates versus persistence factors (e.g., temperature, resistance to grazing, etc.)…”
Section: Seasonal Dynamics Of Enterovirus Infectionsmentioning
confidence: 99%
“…The EV distributions described here could also be reflective of differential persistence rates among EV species in municipal wastewater between households and primary treatment. Previous studies have reported variable rates of persistence among EV in wastewater sludge (54)(55)(56), but controlled studies comparing species-specific differences are lacking. Such information is necessary to help determine the relative levels of importance of seasonal shedding rates versus persistence factors (e.g., temperature, resistance to grazing, etc.)…”
Section: Seasonal Dynamics Of Enterovirus Infectionsmentioning
confidence: 99%
“…Similarly, it appears that virus survival in sludge-amended soils is controlled primarily by desiccation and soil tem perature [69,82]. During surface application of digested sludge on soils in Pensacola, Florida, it was shown that indigenous enteroviruses were able to survive only 9 days after sludge application [83].…”
Section: Field Studies On Microbial Survivalmentioning
confidence: 99%
“…In this regard, taking advantage of the unsaturated zone as a means of protecting groundwater from viral transport by retention (Chu et al, 2003) was demonstrated by Farrah et al (1981). It was shown that enteroviruses introduced as tracers were efficiently retained by a sludge soil mixture and, therefore, not detected in deep wells located on the sludge disposal site or in a nearby lagoon.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a significant diversity among the enteroviruses in the sludge soil mixture was observed. During the initial part of the examination, poliovirus accounted for more than 90 percent of the viruses in the sludge, whereas later, it was determined that echoviruses and coxsackieviruses were the most common enteroviruses identified (Farrah & Preston, 1985;Farrah et al, 1981).…”
Section: Introductionmentioning
confidence: 99%